Um estudo do icosaedro a partir da visualização em geometria dinâmica - Palles, Camila Molina (2013)
This research aims at studying the geometrical visualizations of the dynamic figural registers through Duval`s Theory of Register of Semiotics Representation, whose main goal is to answer the following question: "What elements essential for the development of visualization are present in an instructional sequence to construct the formula for calculating the measure of the volume of the icosahedron by means of Cabri-3D?".In order to find the answer to the question that has been proposed, we have investigated a case study because of its empirical nature which can be based on a documental analysis, taking a didactic sequence case study for the calculus of the volume of the Icosahedron, which is commonly discussed in Possani (2012). Sequence analysis from the factors explained by Duval (2004) led us to conclude that the sequence developed, for the most part, does not allow the development of visualization. However, it is possible to conjecture some modifications to this sequence which then allow the development of view